The Relationship Between Plant-Based Diet and Risk of Digestive System Cancers: A Meta-Analysis Based on 3,059,009 Subjects - Zhao, Yujie; Zhan, Junyi; Wang, Yongsen; Wang, Dongli (Frontiers in Public Health, 2022)
Background and Objectives Diets containing red or processed meat are associated with a growing risk of digestive system cancers. Whether a plant-based diet is protective against cancer needs a high level of statistical evidence. Methods We performed a meta-analysis of five English databases, including PubMed, Medline, Embase, Web of Science databases, and Scopus, on October 24, 2021 to identify published papers. Cohort studies or case-control studies that reported a relationship between plant-based diets and cancers of the digestive system were included. Summary effect-size estimates are expressed as Risk ratios (RRs) or Odds ratios (ORs) with 95% confidence intervals and were evaluated using random-effect models. The inconsistency index (I2) and τ2 (Tau2) index were used to quantify the magnitude of heterogeneity derived from the random-effects Mantel-Haenszel model. Results The same results were found in cohort (adjusted RR = 0.82, 95% CI: 0.78–0.86, P < 0.001, I2 = 46.4%, Tau2 = 0.017) and case-control (adjusted OR = 0.70, 95% CI: 0.64–0.77, P < 0.001, I2 = 83.8%, Tau2 = 0.160) studies. The overall analysis concluded that plant-based diets played a protective role in the risk of digestive system neoplasms. Subgroup analyses demonstrated that the plant-based diets reduced the risk of cancers, especially pancreatic (adjusted RR = 0.71, 95% CI: 0.59–0.86, P < 0.001, I2 = 55.1%, Tau2 = 0.028), colorectal (adjusted RR = 0.76, 95% CI: 0.69–0.83, P < 0.001, I2 = 53.4%, Tau2 = 0.023), rectal (adjusted RR = 0.84, 95% CI: 0.78–0.91, P < 0.001, I2 = 1.6%, Tau2 = 0.005) and colon (adjusted RR = 0.88, 95% CI: 0.82–0.95, P < 0.001, I2 = 0.0%, Tau2 = 0.000) cancers, in cohort studies. The correlation between vegan and other plant-based diets was compared using Z-tests, and the results showed no difference. Conclusions Plant-based diets were protective against cancers of the digestive system, with no significant differences between different types of cancer. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022322276, Identifier: CRD42022322276.